Literasi Membaca dan Menulis Untuk Anak Usia Dini di Rumah Ajare Desa Saunulu - Samel Sopakua; Aby Mamangsa; Kiky Lekantompessy; Fransiska Kristi Widari; Atry Pattilemonia; Novita L. Sahertian (Abdimas Universal, 2023)
This article describes literacy for early childhood which is carried out to prepare them to enter elementary school. The aim of the activity is focused on disadvantaged, poor areas, and aspects of education that have not been touched upon by services. Most of the parents and children in Mangga Dua hamlet are still illiterate. It is hoped that through this activity, awareness of reading and writing can be increased so that children can continue their education at primary school level and can build high awareness, concern and responsiveness from the local community. The service uses the assistance method of reading and writing practice for approximately 3 days and training for the managers of Rumah Ajare. Outreach was provided to the local community regarding the importance of reading and writing literacy education for children. This activity is a motivation for the government to pay attention to transportation facilities and educational infrastructure for local communities. It is hoped that the provision of assistance in the form of reading books and stationery equipment by the community service team can also increase the activities of school children at Rumah Ajare.